THE JUDICIAL REVIEW OF CONTRACTS AS ACCESS TO JUSTICE: AN ANALYSIS OF SOCIAL FUNCTION SINCE THE LAW 13.874/2019 (Revista Paradigma, 2022)
The Law 13.874/2019 was justified under the arguments of desbureaucratization and social and economic development through the market liberalisation. On this way, it changed the Civil Code rules on social function and judicial review of contract, based in an apparent paradox between the principles of social function and judicial review of contracts and the principles of contractual freedom, legal security and private autonomy. So, this paper aims to demonstrate, using deductive methodology, the theoretical misconception on which is based the premises of the law, arguing that the social function and judicial review of contracts are not incompatibles with the traditional principles of general theory of contracts. In conclusion, the legal changes of Law 13.874/2019 can spread the culture of consensual solution of conflicts.